Novelty during a late postacquisition time window attenuates the persistence of fear memory - Katche, Cynthia Lorena (2016)
Learning to avoid threats in the environment is highly adaptive. However, sometimes a dysregulation of fear memories processing may underlie fear-related disorders. Despite recent advances, a major question of how to effectively attenuate persistent fear memories in a safe manner remains unresolved. Here we show experiments employing a behavioural tool to target a specific time window after training to limit the persistence of a fear memory in rats. We observed that exposure to a novel environment 11 h after an inhibitory avoidance (IA) training that induces a long-lasting memory, attenuates the durability of IA memory but not its formation. This effect is time-restricted and not seen when the environment is familiar. In addition, novelty-induced attenuation of IA memory durability is prevented by the intrahippocampal infusion of the CaMKs inhibitor KN-93. This new behavioural approach which targets a specific time window during late memory consolidation, might represent a new tool for reducing the durability of persistent fear memories.